The efficacy of hypnosis intervention in alleviating the psychological and physical symptoms during pregnancy, labour, and postpartum / Zuhrah Beevi Kunji Ahmad - Zuhrah Beevi, Kunji Ahmad (2016)
Physical and psychological symptoms during pregnancy are common. Various strategies such as hypnosis are available to reduce these symptoms. This study investigates the efficacy of hypnosis intervention in alleviating the psychological and physical symptoms during pregnancy and labour as well as postpartum. A quasi-experimental design was utilised in this study with 56 patients (28 participants in the experimental group and 28 participants in the control group). Hypnosis intervention was given to the experimental group participants at weeks 16, 20, 28 and 36 of pregnancy. Participants in the control group received only the routine antenatal care from the obstetricians, with some form of attention control from the healthcare professionals, such as breathing techniques. Participants from both groups completed the Depression Anxiety Stress Scale – 21 (DASS-21) and Pregnancy Symptoms Checklist at weeks 16, 20, 28 and 36 of pregnancy. Participants in the experimental group completed the DASS-21 and the Pregnancy Symptoms Checklist during the hypnosis sessions, and participants in the control group completed the questionnaires during their routine antenatal check-up. Participants’ systolic and diastolic blood pressure measurements and foetal weight at week 36 of pregnancy were collected. Data collected during the labour stage consisted of the length of second and third labour stages, pain relief used during labour (e.g. pethidine), delivery methods, and assisted vaginal delivery. Within 24 hours of delivery, data pertaining to neonatal birth weight, neonatal Apgar scores, and self-reported pain were obtained. At two months postpartum, participants from both the experimental and control groups completed the DASS-21 and the Edinburgh Postpartum Depression Scale (EPDS). The results of the pregnancy stage indicated that the experience of antenatal stress and anxiety symptoms for the experimental group had decreased from baseline to week 36 of pregnancy. However, for the control group, antenatal stress and anxiety symptoms had decreased and later increased at week 36. Meanwhile the experience of depressive symptoms for the experimental group had slightly increased at week 36. The mean of antenatal physical symptoms for the participants in the control group was higher than for the participants in the experimental group. The group differences on antenatal stress, anxiety, and physical symptoms at week 36 of pregnancy were significant (p<.05), and not significant for depressive symptoms (p>.05). The results of the pregnancy stage had also indicated that the experimental group participants’ foetal weight at week 36 of pregnancy was higher, and the group differences were significant (p<.05). However, the group differences in systolic and diastolic blood pressure at week 36 were not significant (p>.05). The results of the labour stage showed no significant differences in the length of second and third stages of labour. The group differences in pethidine used were significant (p<.05), with the experimental group participants opting for less pethidine. None of the experimental group participants had opted for epidural, and more participants in the control group had assisted vaginal deliveries and caesarean sections. More participants in the experimental group had given birth naturally. Results within 24 hours postpartum showed that more neonates in the experimental group had higher Apgar scores. Group differences in neonatal weight were not significant (p>.05). Participants in the experimental group had experienced higher pain just before, during, and right after delivery. The results at two months postpartum showed that the experimental group had higher mean of postpartum stress, but lower means of postpartum anxiety and depressive symptoms. The group differences on postpartum anxiety and depressive symptoms were significant (p<.05), and were not significant for postpartum stress (p>.05). Finally, the group differences on postpartum depression were significant (p<.05), and the results indicated that the experimental group had experienced reduced postpartum depression. Thus, alleviation of physical and psychological symptoms during pregnancy via hypnosis ensures a better experience throughout pregnancy, labour and postpartum.